Evaluasi Ticketing MRT Jakarta Mobile Apss dengan Menggunakan Model DeLone dan McLean: Evaluation of MRT Jakarta Mobile Apps Ticketing Using the DeLone and McLean Model - Mukti Khamid, Anugrah; Leliana, Arinda; Raden Roro Siti Kuswati , Atik (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
The MRT Jakarta has three methods of ticket payment, i.e. Ticket Vending Machine, E-Money Tap Card, and by apps using MRTJ mobile apps. Some issues came from the passengers complaining about the simplicity of purchasing MRTJ ticket using this app. Passengers are confused when using this apps, while using another payment method is faster and more efficient. This research was conducted by evaluating information system success on the MRTJ mobile apps application using the Delone & McLean model approach with the correlation of 6 variables, including information quality, system quality, service quality, use, user satisfaction, and net benefit with the structural equal model method using the SmartPLS application. The analysis was carried out in two stages: the measurement model (outer model) and the structural model (inner model). In the outer model test, two indicators in the system quality variable do not pass the validity requirements, so they need to be excluded from these variables. All variables are proven to have an influence on the application, but the information quality variable on the use variable and the information quality variable on user satisfaction have a tendency to negatively influence based on the path coefficient value determined by the p-value and t-statistic values so that it does not fulfil the predetermined hypothesis.